2005
DOI: 10.1002/bit.20690
|View full text |Cite
|
Sign up to set email alerts
|

Influence of secondary reactions on the synthetic efficiency of DHAP‐aldolases

Abstract: The effect of secondary reactions on DHAP-dependent aldolase stereoselective synthesis yields is reported. The fuculose-1-phosphate aldolase catalyzed synthesis between DHAP and Cbz-S-alaninal has been chosen as case study. It has been demonstrated that DHAP is not only chemically degraded in the reaction medium, but also enzymatically. The last reaction has been shown to take place when type II aldolases are used as biocatalysts. In order to minimize the effect of non-desired reactions, temperature reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…[37] Investigations of temperature effects: Temperature effects were also investigated for RhuA aldolization of aldehydes (R)-2 a, (R)-2 b (vide infra), (R)-2 c, (R)-2 f, and (S)-2 f. To this end, the selected reactions were conducted at 4 8C, because it has been reported that at this temperature the conversion achieved on FucA-catalyzed aldol addition of DHAP to (R)-N-Cbz-alaninal was significantly improved. [38] Interestingly, there were temperature effects on the stereoselectivity of the enzymatic reactions (vide infra), but no improvement on aldol conversions was observed for any of the selected examples, indicating that this phenomenon is not of general applicability.…”
Section: Resultsmentioning
confidence: 98%
“…[37] Investigations of temperature effects: Temperature effects were also investigated for RhuA aldolization of aldehydes (R)-2 a, (R)-2 b (vide infra), (R)-2 c, (R)-2 f, and (S)-2 f. To this end, the selected reactions were conducted at 4 8C, because it has been reported that at this temperature the conversion achieved on FucA-catalyzed aldol addition of DHAP to (R)-N-Cbz-alaninal was significantly improved. [38] Interestingly, there were temperature effects on the stereoselectivity of the enzymatic reactions (vide infra), but no improvement on aldol conversions was observed for any of the selected examples, indicating that this phenomenon is not of general applicability.…”
Section: Resultsmentioning
confidence: 98%
“…(S)-Cbz-alaninal was synthesized in our laboratory by 2-iodobenzoic acid oxidation of the corresponding N-protected amino alcohol as reported in literature [14,15,17].…”
Section: Methodsmentioning
confidence: 99%
“…In previous work [15], the significance of chemical and enzymatic DHAP degradation in class II aldolase-catalyzed syntheses has been reported, employing the above mentioned synthesis catalyzed by FucA. Published results using recombinant His-tagged FucA produced in our laboratory, led to the synthesis product with a 100% diastereomeric excess [16].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, DHAP is chemically unstable, particularly under alkaline conditions, and decomposes into inorganic phosphate and methyl glyoxal, both of which may inhibit the aldolase. DHAP degradation can be considerably reduced by lowering the reaction temperature to 4 • C, which constitutes an optimum between residual aldolase activity and minimum rate of DHAP loss [78]. Furthermore, if the phosphate group must be removed from the final product, the use of DHAP reduces significantly the atom economy of the process.…”
Section: Dihydroxyacetone Phosphate (Dhap) Aldolasesmentioning
confidence: 99%